Promising Pathways: Investigating Personal Factors Promoting Nonprofit Executives (Journal of Public and Nonprofit Affairs, 2021)
The nonprofit sector has been critiqued for failing to systematically develop leadership to meet the sector’s professionalizing needs. The personal profile of who sits in the nonprofit executive position can be insightful about what experience and training have been deemed appropriate for nonprofit leadership and may reveal career pathways to the executive position. In this paper, the career backgrounds of 185 nonprofit association executives are reported upon, investigating if the credentials and experience held by these executives helped expedite their career pathway to the top position. The findings indicate that nonprofit sector experience was a significant predictor of time to the executive position, but that other career variables, such as education, credentials, and other previous experiences did not significantly impact the time to the position. This study adds to what we know about the professionalization of the nonprofit sector and raises questions about what signals readiness for the sector’s executive position.